REVIEW ARTICLEThe role of excitotoxicity in neurodegeneration - Salińska, Elżbieta; Danysz, Wojciech; Łazarewicz, Jerzy W. (Folia Neuropathologica, 2005)
A body of evidence suggests that the mechanisms of excitotoxic neuronal damage evoked by excessive or prolonged activation of the excitatory amino acid receptors may be involved in pathogenesis of brain damage in acute insults and in chronic neurodegenerative diseases. In this review we briefly discuss several selected mechanisms of the excitotoxicity, focusing attention on the role of ionotropic glutamate receptors, calcium transients and calcium-mediated cell injury. In the second part of this paper we provide information on elements of excitotoxicity in brain diseases.